Entrepreneurship skills development in higher education courses for teams leaders - Maria José Sousa (Administrative Sciences, 2018)
This article analyses the concept of skills and identifies the skills needed by entrepreneurs to lead their teams. To accomplish these goals, the primary step was to determine the leadership skills developed by the universities in the entrepreneurship and innovation courses and to compare it with the needed skills perceived by entrepreneurs. This research approach is framed in the Management Sciences, and the research problem is anchored to the following research questions: What leadership skills are required by students for them to be effective in entrepreneurial endeavors upon graduation? Are the skills identified by the entrepreneurs sufficiently learned in Universities in Portugal? Does the student work experience, gender or age contribute to a level of leadership skills attainment? The leadership skills identified by the entrepreneurs were pointed out by two focus groups with 15 entrepreneurs and by conceptual content analysis, establishing the existence and frequency of concepts represented by the words or phrases in the entrepreneur's discourse. To verify if those skills are being developed in the entrepreneurship and innovation of higher education courses, an online survey was conducted with the students from the 3rd year of 2016/2017 academic year of several universities. The primary outcome of the research will be a proposal for a model of leadership skills development for students to potentiate their leadership capacity as entrepreneurs.
Keywords: 350; skills; higher education; entrepreneurship; leadership; teams